Diversity oriented total synthesis (DOTS) of pyridoquinazolinone alkaloids and their analogues - Sivappa Rasapalli; Yanchang Huang; Vamshikrishna Reddy Sammeta; Reem Alshehry; Fazmina Anver; James A. Golen; Shivasankar Krishnamoorthy; Subhash P. Chavan (Tetrahedron Chem, 2024)
A short diversity oriented total synthesis (DOTS) of substituted rutaecarpines, homo-luotonins, homo-vasicinone, homo-isaindigotones and homo-vasnetine has been achieved from the key tricyclic intermediate. The [6,6,6] tricyclic ketone, the mackinazolindione, was accessed from simple substrates i.e., quinazolinone diester obtained from the disubstituted anthranilamide which in turn was prepared from the coupling of amino acid ester and ethyl oxalyl chloride with isatoic anhydride and Dieckmann condensation chemistry.